Aspirin history and its clinical applications in pregnancy - Kumar, Mukesh; Gupta, Nitesh Kumar; Kumari, Monika; Abhishake, Bharti; Shah, Ravi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Aspirin (acetylsalicylic acid), derived from salicylate-containing plants and refined through major chemical advances in the 19th century, remains one of the most widely used NSAIDs. Its irreversible inhibition of COX-1 reduces thromboxane A₂ production, producing sustained antiplatelet effects central to its therapeutic use. Hypertensive disorders of pregnancy are major contributors to maternal and perinatal illness and death globally, with preeclampsia posing a significant clinical challenge. Low-dose aspirin (LDA) is extensively studied in pregnancy and is recommended for preventing preeclampsia, with strong evidence demonstrating reduced maternal and perinatal morbidity, particularly when initiated before 16 weeks. Additional benefits include lower rates of preterm birth, improved foetal growth in selected cases of IUGR, and enhanced pregnancy outcomes in women with APS and SLE when used alone or in combination with heparin. Major guidelines from ACOG, NICE, RCOG, WHO, and FIGO support LDA use in high-risk pregnancies.